Ribociclib plus fulvestrant for advanced breast cancer: Health-related quality-of-life analyses from the MONALEESA-3 study. (December 2020) - Fasching, Peter A.; Beck, J. Thaddeus; Chan, Arlene; De Laurentiis, Michele; Esteva, Francisco J.; Jerusalem, Guy; Neven, Patrick; Pivot, Xavier; Bianchi, Giulia V.; Martin, Miguel; Chandiwana, David; Lanoue, Brad; et al.
Abstract: Purpose: In the MONALEESA-3 Phase III trial of patients with hormone receptor–positive human epidermal growth factor receptor–negative advanced breast cancer, ribociclib plus fulvestrant significantly improved progression-free survival (PFS) and overall survival (OS). Here, we present patient-reported outcomes from the trial, including health-related quality of life (HRQOL). Methods: Patients were randomized (2:1) to receive ribociclib plus fulvestrant or placebo plus fulvestrant. Time to definitive 10% deterioration (TTD) from baseline in HRQOL (global health status [GHS] from the EORTC QLQ-C30 questionnaire) and pain (BPI-SF questionnaire) were assessed using Kaplan-Meier estimates; a stratified Cox regression model was used to estimate the hazard ratio (HR) and 95% CIs. Results: Deterioration ≥10% in the EORTC-QLQ-C30 GHS was observed in 33% of patients in the ribociclib group vs 34% of patients in the placebo (reference) group (HR for TTD ≥ 10% = 0.81 [95% CI, 0.62–1.1]). Similar findings were noted for TTD ≥5% (HR = 0.79 [95% CI, 0.61–1.0]) and TTD ≥15% (HR = 0.81 [95% CI, 0.60–1.08]). TTD ≥10% in emotional functioning (HR = 0.76 [95% CI, 0.57–1.01]) trended in favor of the ribociclib group, whereas results for fatigue and pain were similar between arms. TTD ≥10% in BPI-SF pain severity index score (HR = 0.77 [95% CI, 0.57–1.05]) and worst pain item score (HR = 0.81 [95% CI, 0.58–1.12]) trended in favor of ribociclib vs placebo. Conclusions: In addition to significantly prolonging PFS and OS compared with placebo plus fulvestrant, adding ribociclib to fulvestrant maintains HRQOL. Highlights: Ribociclib + fulvestrant allowed maintenance of global health status (GHS). Time to deterioration (TTD) by 10% can convey duration until worsening of QOL. TTD ≥10% was delayed with ribociclib in GHS and emotional functioning. Ribociclib also demonstrated trends toward delayed TTD vs placebo in pain outcomes.